PERSEPSI MASYARAKAT TERHADAP SISTEM PENDIDIKAN PESANTREN DI KOTA SERANG BANTEN - Ima Maisaroh; Iwan Ridwan (Jurnal Pendidikan Karakter JAWARA (Jujur, Adil, Wibawa, Amanah, Religius, Akuntabel), 2021)
Product Image packaging usualy effective in making of public perception and influence in decision rule. the decision which people made for education is influenced by many factor, but usually the dominant factor is perception. This research is to know about people perception to the Pesantren Education System. Knowing people perception as an nucleus aspect of development and knowing people perception to the Pesantren Education System as a sub system of National Education System is relevant and needed. The method used in this Explorative Reseacrh is Description-Quantitative and combine with Grounded Reseacrh which Hypothesis Research stated as : The Perception of the people of Keluruhan Sukawana Kecamatan – Kota Serang Banten to the system of Pesantren Education is Positive”. Sample is 10 % of 100 person of population (50 women and 50 men) take by Purposive Sampling Method, and Processed and analyzed with sample statistic using Tabulation, Ordinal score, Likert Scale and Perception Scale. The mention purpose and benefit of this research can be reach as important input for the direction of the development of Pesantren Education in order to become a systematic and perfect improvement, properly with people needs and nation interests. The final score likert are as follows : a. Women Participation = 4.309 94 %; b. Men Participation = 4.463 94 % and c. People Participation = 8.772 94 %. After confirmed to the participation categorical scale so the reseach hypothesis to the Pesantren Education of Banten People to the Pesantren Education system is Positive.